An APS software selection methodology integrating experts and decisions-maker's opinions on selection criteria: A case study. Issue 1 (1st January 2019) - Piengang, Fabrice Chilly Ngamaleu; Beauregard, Yvan; Kenné, Jean-Pierre
Abstract: With important advancements achieved in information technology, wide varieties of advanced planning and scheduling (APS) software has emerged in recent decades. Each of those APS software uses their own techniques, algorithms and logic to plan and schedule operations, which makes the task of evaluating them very difficult. However, choosing the right APS software is critical for companies because of significant resources engaged and risk of disturbing operations. Presently, a clear, structured and rational approach is lacking in the literature for APS software selection. The main contribution of this paper is to fill this gap by developing an APS software selection methodology. The methodology is based on fuzzy quality function deployment (QFD) and two well-known multiple criteria decision-making (MCDM) techniques, analytic hierarchy process (AHP) and VIKOR. This work considers both company needs and APS selection criteria to build a hybrid hierarchical decision structure. House of quality helps in translating the relevance of the company needs in the evaluation of criteria. Triangular fuzzy numbers are also used to reduce uncertainties in the process. An application of the proposed methodology to an aero-derivative gas turbine case company is carried out to demonstrate the useful and easy implementation of the proposed methodology.